Adsorption of zinc (Zn2+) from aqueous solution on natural bentonite - Sen, Tushar Kanti; Gomez, Dustin (Elsevier BV, 2011)
The adsorptive properties of natural bentonite in the removal of zinc (Zn2+) from aqueous solution were studied. The results show that the amount of adsorption of zinc metal ion increases with initial metal ion concentration, contact time, and solution pH but decreases with the amount of adsorbent and temperature of the system. Kinetic experiments clearly indicate that adsorption of zinc metal ion (Zn2+) on bentonite is a two step process: a very rapid adsorption of zinc metal ion to the external surface is followed by possible slow decreasing intraparticle diffusion in the interior of the adsorbent which has also been confirmed by intraparticle diffusion model. Overall the kinetic studies showed that the zinc adsorption process followed pseudo-second-order kinetic model. The different kinetic parameters including rate constant, half adsorption time, and diffusion coefficient are determined at different physicochemical conditions. The equilibrium adsorption results are fitted better with Langmuir isotherm compared to Freundlich models. The value of separation factor, RL from Langmuir equation and Freundlich constant, n both give an indication of favorable adsorption. Finally in thermodynamic studies, it has been found that the adsorption process is exothermic due to negative ∆H0 accompanied by a decrease in entropy change and Gibbs free energy change (∆G0).